Impact of proteostasis workload on sensitivity to proteasome inhibitors in multiple myeloma - Sedlacek, Jindrich (Clinical and experimental medicine, 2025)
Genomic alterations and enormous monoclonal immunoglobulin production cause multiple myeloma to heavily depend on proteostasis mechanisms, including protein folding and degradation. These findings support the use of proteasome inhibitors for treating multiple myeloma and mantle cell lymphoma. Myeloma treatment has evolved, especially with the availability of new drugs, such as proteasome inhibitors, into therapeutic strategies for both frontline and relapsed/refractory disease settings. However, proteasome inhibitors are generally not effective enough to cure most patients. Natural resistance and eventual acquired resistance led to relapsed/refractory disease and poor prognosis. Advances in the understanding of cellular proteostasis and the development of innovative drugs that also target other proteostasis network components offer opportunities to exploit the intrinsic vulnerability of myeloma cells. This review outlines recent findings on the molecular mechanisms regulating cellular proteostasis pathways, as well as resistance, sensitivity, and escape strategies developed against proteasome inhibitors and provides a rationale and examples for novel combinations of proteasome inhibitors with FDA-approved drugs and investigational drugs targeting the NRF1 (NFE2L1)-mediated proteasome bounce-back response, redox homeostasis, heat shock response, unfolding protein response, autophagy, and VCP/p97 to increase proteotoxic stress, which can improve the efficacy of antimyeloma therapy based on proteasome inhibitors.
Keywords: homeostáze proteinů; chemorezistence; Redox homeostasis; Proteasome Inhibitors; mnohočetný myelom; Autophagy; UPR; protinádorové látky; Proteostasis; Humans; inhibitory proteasomu; Multiple Myeloma; Drug Resistance, Neoplasm; Antineoplastic Agents; VCP/p97; Proteasome bounce-back response; lidé; Heat shock response